Development of a Calorie Calculator Application Utilizing Height and Weight-Based Conversion - Junior Maulidiansyah; Mohammad Rofi’i; Wisnu Adi Prasetyanto (Jurnal Kesehatan dan Kedokteran, 2025)
The advancement of information technology has significantly contributed to innovations in the health sector, including the development of digital tools that support nutrition management and healthy lifestyle practices. One essential aspect of maintaining health is managing daily caloric intake based on individual metabolic needs, which are influenced by factors such as age, gender, height, weight, and physical activity. However, many individuals are unaware of how to accurately calculate their caloric requirements. Therefore, a practical and accurate system is needed to provide personalized calorie recommendations.This study presents the design and development of an Android-based calorie calculator application that estimates daily energy needs using user inputs: age, gender, height, weight, and activity level. The application integrates two well-known formulas—Harris-Benedict and Mifflin-St Jeor—to calculate Basal Metabolic Rate (BMR) and determines Total Daily Energy Expenditure (TDEE) by categorizing physical activity as light, moderate, or intense. In addition, the app includes a Body Mass Index (BMI) calculator to indicate the user's nutritional status. Developed using the Kotlin programming language in Android Studio, the application is designed with a user-friendly interface to enhance user experience. Functionality testing demonstrated that the application provides accurate estimations of caloric needs and reliable BMI categorization based on user input. The outputs are consistent with results from existing online calorie calculators, confirming its precision and usability. This calorie calculator application is expected to function both as an educational and practical tool for individuals seeking to adopt a balanced diet and effective weight management strategy.